Performance and emission characteristics of a CI engine using graphene oxide (GO) nano-particles additives in biodiesel-diesel blends - Hoseini, S. S.; Najafi, G.; Ghobadian, B.; Ebadi, M. T.; R., Mamat; Yusaf, T. (Elsevier, 2020)
In the present study, the effects of graphene oxide (GO) nano-particles on performance and emissions of a diesel engine fueled with Oenothera lamarckiana biodiesel was investigated. Biodiesel was used in the blend of B20. The GO nano-particles with concentrations of 30, 60, and 90 ppm were considered for each fuel blend. Experiments were performed at a constant speed of 2100 rpm at loads of 0%, 25%, 50%, 75%, and 100%. Various parameters, such as power, exhaust gas temperature (EGT), carbon monoxide (CO), carbon dioxide (CO2), unburned hydrocarbons (UHCs), and nitrogen oxides (NOx), were investigated. Results showed that by using GO, power and EGT significantly increase. Furthermore, by using GO nano-particles, significant reductions in CO (∼5%–22%) and UHCs (∼17%–26%) were observed. However, under similar conditions, a slight increase in CO2(∼7%–11%) and NOx (∼4%–9%) emissions observed. Finally, it can be concluded that nano-graphene oxide can be introduced as a suitable alternative fuel additive for Oenothera lamarckiana biodiesel blends.